Genetics of Durable Resistance to Leaf Rust in Bread Wheat Cultivars Capelle Desprez and Pari 73 - R. G. Saini, Priti Sharma* and (Journal of Phytology, 2011)
Bread wheat cultivars Capelle Desprez and Pari 73 have been showing adult plant leaf rust resistance in India since 20 years. To examine nature, number and mode of inheritance to leaf rust multipathotype tests were conducted on these cultivars along with reference line RL6058 and HD2009 and the susceptible cultivars WL711 and Agra Local at adult plant stages against the eight leaf rust races. F2 and F3 generations from crosses of Capelle Desprez and Pari 73 with susceptible cultivar WL711 were tested for percent disease severity against leaf rust race 77-5 which suggested the presence of three genes in Capelle Desprez and two genes in Pari 73 to leaf rust. Allelic tests using Capelle Desprez with RL6058 indicated the presence of linked genes Lr34/Yr18 however, presence of transgressive segregants in this cross indicated that the other two genes in Capelle Desprez are also involved in leaf rust resistance. The segregation for susceptible plants observed among all the crosses used for allelic tests of Pari 73 for leaf rust indicated that non-hypersensitive resistance genes in Pari 73 are different from those in RL6058, HD2009 and Capelle Desprez. Studies using 536 primers indicated that one of the three rust resistance gene(s) in cultivar Capelle Desprez is located on chromosome 1B, at a distance of 26.3cM from the primer Xgwm 268. Chromosome location of leaf rust resistance gene from cultivar Pari 73 could not be achieved.